PENGARUH PENGETAHUAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA CV.RIA BUSANA: Manajemen sumberdaya manusia - Tedi Pitri, SIP., MM (P3M STIE PASIM Sukabumi, 2020)
Humans are the most important resource in an organization, agency or company without human aspects, it is difficult for the organization to carry out the mission and goals that have been set. It can also be said that if the human factor does not exist, the organization concerned does not exist because of the actor or object that an organization intends to aim at. In improving the quality of employee performance, the company can do various ways, one of which is by increasing knowledge of employees and providing explanations to employees so that they can know and master what they are doing, so that the company will get employee performance results that match the company's expectations.This research is intended to determine the effect of employee knowledge and work experience on employee performance of CV Ria Busana. The type of data in this thesis is primary data. The collected data is then processed and analyzed. The results of hypothesis testing are found that the variable reliability simultaneously influences the (quality of employee work).